PENGARUH WORD OF MOUTH DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA UNIVERSAL PHOTO STUDIO PEKANBARU - Anisa Gusanasari; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The research conducted at Universal Photo Studio Pekanbaru where located in JL. HR. Soebrantas Panam No. 81, Sidomulyo Bar, Tampan, Kota Pekanbaru. This study aims to determine the effect of word of mouth and pricing on purchase decisions at universal photo studio pekanbaru. In this study use quantitive descriptive with SPSS program. The population in this is are consumers at universal photo studio pekanbaru. The sampling technique chosen is slovin Formula with a sample 88 respondents. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that Word of mouth and pricing have a positive and significant effect on purchase decision at universal photo studio pekanbaru. With the calculation of the coefficient of determination (R2) word of mouth on purchase decision the value of R square is 0,575 or 57,5% and pricing on purchase decision the value of R square is 0,555 or 55,5% and coefficient of determination (R2) word of mouth and pricing on purchase decision the value of R square is 0,657 or 65,7%. This show that the word of mouth and pricing gives an effect of 65,7% on purchase decision at universal photo studio pekanbaru, while remaining 34,3% is effected by other variables that are not examined in this study.Key words: Word of mouth, Pricing, Purchase Decision